Lumbar spondylolysis in pediatric and adolescent soccer players - El Rassi, G.; Takemitsu, M.; Woratanarat, P.; Shah, S. A. (The American Journal of Sports Medicine, 2005)
Background: Lumbar spondylolysis in young soccer players has not been studied extensively.